The Effect of Long Shelf Life of Duroc Pig Male Semen Diluted Using Tris-Egg Yolk-Young Coconut Water on The Value of Viability, Abnormality and pH - Berek, Fransiska Luruk; Dethan, Agustinus Agung; Tahuk, Paulus Klau (Journal of Tropical Animal Science and Technology, 2021)
This study aims to determine the effect of shelf life of duroc boar semen which was diluted using tris-egg yolk-coconut water thinner on the value of viability, abnormality, and acidity (pH). The semen used is in the form of fresh semen from 2-year-old duroc pigs. Semen was collected by a manual method using artificial broodstock. This research was conducted in November 2020 using an experimental method according to the Completely Randomized Design (CRD) procedure with 4 treatments and 4 replications so that there were 16 experimental units. Each treatment is P0: storage of semen for 0 hours, P1: storage of semen for 24 hours, P2: storage of semen for 36 hours, P3: storage of semen for 48 hours. The results showed that the use of tris-egg yolk-coconut water diluent had a significant effect (P <0.05) on viability, abnormality, and degree of acidity (pH). The mean value of spermatozoa viability was P0: 96%, P1: 93.75%, P2: 84.5%, and treatment P3: 79.5%. The mean value of spermatozoa abnormality in treatment P0: 5.25%, P1: 6.5%, P2: 11.25%, and treatment P3: 14.75%. The average value of the degree of acidity (pH) of semen P0: 8.3 P1: 7.2; P2 7,3 and P3 treatment: 7,25. It can be concluded that the dilution of semen using tris-egg yolk and coconut water can maintain the value of viability, abnormalities of spermatozoa, and degree of acidity (pH).